2018
DOI: 10.5812/aapm.74026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Consumption of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Antagonists on Blood Pressure and Inotrope Consumption After Separation from Cardiopulmonary Bypass

Abstract: BackgroundChronic use of renin-angiotensin system (RAS) antagonists (angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor antagonists (ARAS)) can cause hypotension during anesthesia. In some studies hemodynamic instability, including hypotension and its effects on the clinical outcome in patients treated with these drugs during coronary artery bypass graft (CABG) and need to excessive vasoactive drugs in these patient population, has been described. The aim of this study was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It showed that the calculated F -value of 564.09 was significantly more than the table value ( p = 0.001). 10…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the calculated F -value of 564.09 was significantly more than the table value ( p = 0.001). 10…”
Section: Discussionmentioning
confidence: 99%